A STUDY OF THE TRANSLATION OF GOOGLE TRANSLATE - Ika Kartika Amilia; Darmawan Eko Yuwono (LINGUA : JURNAL ILMIAH, 2020)
ABSTRACT This study is intended to analyze errors made by Google Translate in translating Eliza Riley’s Return to Paradise short story. The method is qualitative descriptive. The data are collected by comparing the translation of Google Translate with that of a professional translator. The errors are analyzed based on Mossop’s revision parameters. The findings show that Google Translate failed to recognize idiomatic expressions which caused fatal errors in the target text; errors in word choice that caused word translated out of context; and illogical sentence at the target text caused by cultural difference. As a conclusion, Google Translate may be useful to help translate few words, phrase, and particular sentence in general, and also gives a general comprehension in translating text. However, it may not give an adequate result as a fine translation product. Keyword: google translate, error analysis, Mossop’s revision parameters